2020
DOI: 10.1002/er.5752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of using betalain, anthocyanin and chlorophyll dyes together as a sensitizer on enhancing the efficiency of dye‐sensitized solar cell

Abstract: The paper explored the mechanism of working of dye sensitizers for the improvement of efficiency of environmentally benign dye-sensitized solar cells (DSSC). The identified natural dyes namely anthocyanin (A), betalain (B) and chlorophyll (C) were extracted from Roselle (Hibiscus sabdariffa L.), spinach (Spinacia oleracea) and beetroot (Beta vulgaris) respectively. Light absorption performance of dyes was recorded by ultraviolet-visible (UV-vis) spectroscopic analysis followed by direct and indirect band gap c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 54 publications
(121 reference statements)
1
16
0
2
Order By: Relevance
“…The efficiency of betalain-chlorophyll was better than efficiency of DSSCs device using mono-sensitization of betalain i.e., 0.674%. The other result of betalain-chlorophyll cosensitization was also reported by Patni's group research [31]. the combined dye elevated the efficiency of cell device compared to using betalain (η of 1.29%) and chlorophyll (η of 0.95 %) individually.…”
Section: Combining the Betalain Dye With Other Natural Dyes (Co-sensisupporting
confidence: 69%
See 4 more Smart Citations
“…The efficiency of betalain-chlorophyll was better than efficiency of DSSCs device using mono-sensitization of betalain i.e., 0.674%. The other result of betalain-chlorophyll cosensitization was also reported by Patni's group research [31]. the combined dye elevated the efficiency of cell device compared to using betalain (η of 1.29%) and chlorophyll (η of 0.95 %) individually.…”
Section: Combining the Betalain Dye With Other Natural Dyes (Co-sensisupporting
confidence: 69%
“…Once more, this result also showed that higher betaxanthin composition gave significant result in device efficiency and to achieve higher efficiency of device based on betalain dye, the favorable composition is importantly needed. Furthermore, the absorption spectra of betalain dye-TiO2 film (both betaxanthin and betanin) were also reported to have red-shift absorption compare to the absorption of dye in solution state [16,28,31]. This red-shift implied the existence of strong electronic coupling between betalain dye and TiO2 film [16], carrying the possibility to achieve higher DSSCs device efficiency in comparison with other natural dyes.…”
Section: Betalain Dye As Photosensitizer In Dye-sensitized Solar Cellmentioning
confidence: 93%
See 3 more Smart Citations